AKIBAT HUKUM BAGI PELAKU TINDAK PIDANA PELECEHAN SEKSUAL SECARA ONLINE - Danendra Farrel Wicaksono; H.R Adianto Mardjiono (Gapenas Publisher, 2023)
Sexual harassment is an act that can make others feel aggrieved and also make victims affected by prolonged mental stress. Cases of sexual violence and abuse are increasing, although more people do not know about the characteristics. The consequences of this action are difficult to prevent, both for yourself or others in general. Knowing the cause of a person can commit criminal acts of sexual abuse can become one form of effort so that there is no sexual abuse. Sexual harassment actually refers to actions with sexual tone, either through an immediate touch or not touching, which targets a person's body parts or genitals. This activity is usually in the form of whistles, flirting, comment or saying sexual words, showing video or photos of porn and high sexual desires, poke at any part, having sexual movement or making movement in a way that then causes discomfort, violations or feelings. insult, and cause various problems in the health and safety. Sexual harassment is not only about sexual. The core of the problem is to abuse power and authority, although the perpetrator is trying to convince his victim and themselves that what they actually do is sex attraction and romantic desire. But, the majority of male sexual abuse is carried out towards women. Moreover, there were some cases of abuse against women by men and also fellow sexes (male and female). The research method uses the frame analysis method by analyzing cases of sexual harassment reported on the website